2016
DOI: 10.1126/scisignal.aae0549
|View full text |Cite
|
Sign up to set email alerts
|

A peptide of the RGS domain of GRK2 binds and inhibits Gα q to suppress pathological cardiac hypertrophy and dysfunction

Abstract: G protein–coupled receptor (GPCR) kinases (GRKs) play a critical role in cardiac function by regulating GPCR activity. GRK2 suppresses GPCR signaling by phosphorylating and desensitizing active GPCRs, and through protein-protein interactions that uncouple GPCRs from their downstream effectors. Several GRK2 interacting partners, including Gαq, promote maladaptive cardiac hypertrophy, which leads to heart failure, a leading cause of mortality worldwide. The regulator of G protein signaling (RGS) domain of GRK2 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 47 publications
6
51
2
Order By: Relevance
“…These mice show less hypertrophy and less adverse structural remodeling compared with controls (49). In this case, it appears that the beneficial effect is more on Gαq inhibition rather than on GRK2 inhibition.…”
Section: Targeting Grk2 In Heart Failurementioning
confidence: 95%
“…These mice show less hypertrophy and less adverse structural remodeling compared with controls (49). In this case, it appears that the beneficial effect is more on Gαq inhibition rather than on GRK2 inhibition.…”
Section: Targeting Grk2 In Heart Failurementioning
confidence: 95%
“…In this study, the βARKrgs mice were not only resistant to hypertrophic growth after trans-aortic constriction, providing the same anti-hypertrophic effect as inhibition of Gαq association with GPCRs, but the reduction in fibrosis and molecular remodeling prevented the transition to HF during chronic pressure overload (83). This occurred through an association of βARKrgs, but not full-length GRK2, selectively with Gαq in the heart in a manner that inhibited the activity of the Gαq effector phospholipase C beta (PLCβ) (Figure 1-5).…”
Section: Grk2mentioning
confidence: 84%
“…The potential impact of an interaction between the GRK2 RGS domain and Gαq was recently investigated in a mouse model of pressure overload-induced hypertrophy and HF in transgenic mice with αMHC-targeted cardiac expression of this domain (residues 45–185, βARKrgs) (83). In this study, the βARKrgs mice were not only resistant to hypertrophic growth after trans-aortic constriction, providing the same anti-hypertrophic effect as inhibition of Gαq association with GPCRs, but the reduction in fibrosis and molecular remodeling prevented the transition to HF during chronic pressure overload (83).…”
Section: Grk2mentioning
confidence: 99%
See 1 more Smart Citation
“…The N-terminal third also contains a regulator of G protein signaling (RGS) homology (RH) domain. It has been demonstrated that the RH domain of GRK2 and GRK3 is able to interact with Gα q , while the RH domain of GRK5 and GRK6 has not been shown to interact with G-proteins [11, 12]. …”
Section: Introductionmentioning
confidence: 99%